Composite pole piece and preparation method and application thereof
By setting a composite layer of pore-forming agent and ceramic on the surface of the electrode sheet, the problem of degradation of the wetting effect caused by the ceramic coating covering active substances is solved, the safety performance and wetting performance of the battery are improved, and the thermal stability and electrical performance are achieved Chemical properties.
Patent Information
- Application Number
- CN202411467088.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-21
AI Technical Summary
When existing batteries improve the safety performance of the electrode sheet, the ceramic safety coating covers active substances, resulting in a decrease in the wetting effect, affecting the electrochemical performance and safety performance.
A first material layer containing a pore-forming agent and an active substance and a second material layer of ceramics having safety functions are provided on the surface of the electrode sheet. The composite electrode sheet is formed by a double-layer coating technology to improve the safety function and wetting performance of the electrode sheet.
The thermal stability of the composite electrode sheet is improved, the risk of fire and explosion caused by the internal short circuit of the lithium battery is reduced, the manufacturing process is shortened, the manufacturing cost is reduced, and the problem of degradation of wetting performance caused by ceramic coatings is improved.
Smart Images

Figure CN119230728A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite pole piece and a preparation method and application thereof. Background Art
[0002] As the popularity of new energy vehicles continues to increase, the consumer group has an increasingly urgent need to improve the range anxiety and charging anxiety of new energy vehicles, which has accelerated the introduction of battery products with higher energy density and fast charging capabilities. However, in order to ensure the product demand for "fast charging" and "high energy density", how to ensure the safety performance of the battery is the first problem that battery technology workers need to solve.
[0003] Most solutions for improving battery safety performance focus on the cell structure and battery pack design, such as using an inverted cell (explosion-proof valve facing downward) to mitigate the damage to the vehicle when the battery experiences thermal runaway, leaving passengers or drivers with golden time to escape, and adopting structural reinforcement and heat insulation design for the battery pack to enhance the overall safety performance of the battery pack. These measures can effectively improve the safety of new energy vehicle batteries.
[0004] However, improving the intrinsic safety performance of batteries from the material level or the electrode level is still one of the most effective strategies. For example, designing solid-state batteries, using high-safety electrolytes, and using positive electrode materials with lower oxygen release and better thermal stability are all effective means to improve the intrinsic safety of batteries.
[0005] Applying a safety coating is also one of the feasible strategies, such as applying a layer of ceramic on the diaphragm to prepare a ceramic composite diaphragm to improve the puncture strength of the diaphragm. Applying a ceramic coating with a width of 3-10mm on the ear side of the positive electrode can prevent the "internal insertion" of the ear from causing lithium precipitation and improve the burrs of the ear membrane cutting, reduce the risk of internal short, etc. These safety coating measures can effectively improve the safety performance of the electrode and enhance the safety and reliability of the battery cell.
[0006] In addition, there is also a strategy to completely coat the surface of the pole piece with a ceramic layer to thoroughly improve the safety performance of the battery cell (such as patents CN118299674A, CN114141985B, etc.). However, the disadvantage of doing so is that since the active material coating is completely covered by the ceramic safety coating, this will greatly reduce the infiltration of the active material coating with the electrolyte, affecting the infiltration effect. This will inevitably lead to increased time consumption for processes such as liquid injection and high-temperature infiltration (or aging), increased process difficulty, etc. Poor infiltration will eventually cause black spots on the negative electrode sheet and even lithium precipitation when the battery cell is fully charged, affecting the electrochemical performance and safety performance of the battery cell. Summary of the invention
[0007] In view of this, the present application aims to provide a composite electrode, in which a first material layer containing a pore-forming agent and an active substance and a second material layer containing a ceramic with a safety function are sequentially arranged on the surface of the current collector, and both the first material layer and the second material layer contain multiple pores, which can improve the safety function and wetting performance of the electrode.
[0008] Another object of the present application is to provide a method for preparing a composite pole piece.
[0009] Another object of the present application is to provide a secondary battery.
[0010] Another object of the present application is to provide an electrical device.
[0011] To achieve the above objectives, the first aspect of the present application proposes a composite pole piece, comprising:
[0012] current collector;
[0013] A first material layer, the first material layer is disposed on at least a portion of the surface of the current collector, the first material layer comprises an active material and a pore former, the active material comprises a positive electrode active material or a negative electrode active material;
[0014] The second material layer is arranged on at least part of the surface of the first material layer, and the second material layer includes ceramics; the interior and surface of the second material layer and the first material layer are both provided with a plurality of pores formed by thermal decomposition of at least part of the pore-forming agent.
[0015] In some embodiments, the pore-forming agent includes at least one of ammonium carbonate, ammonium bicarbonate, azobisisobutyronitrile, and benzoyl peroxide.
[0016] In some embodiments, the particle size of the pore former ranges from 500 nm to 20 μm.
[0017] In some embodiments, the median particle size of the pore former is 1-5 μm.
[0018] In some embodiments, the mass content of the pore former in the first material layer is 0.1-3%.
[0019] In some embodiments, the positive electrode active material includes at least one of lithium iron phosphate, ternary material, and lithium cobalt oxide.
[0020] In some embodiments, the negative electrode active material includes at least one of graphite, a silicon-carbon composite material, a silicon-oxygen compound, and silicon.
[0021] In some embodiments, the ceramic includes at least one of alumina ceramic and boehmite.
[0022] In some embodiments, the ceramic has a particle size ranging from 100 nm to 5 μm.
[0023] In some embodiments, the ceramic has a median particle size of 0.8-1.2 μm.
[0024] In some embodiments, when the active material includes a positive electrode active material, the material of the first material layer includes the following components in mass percentage: 94-97% positive electrode active material, 0.5-2% first conductive agent, 1-3% first binder, and 0.1-3% pore former.
[0025] In some embodiments, when the active material includes a negative electrode active material, the material of the first material layer includes the following components in percentage by mass: 94-97% negative electrode active material, 0.5-2% second conductive agent, 0.7-2% thickener, 1-2% second binder, and 0.1-3% pore former.
[0026] In some embodiments, the material of the second material layer includes ceramic and a third binder.
[0027] In some embodiments, the first conductive agent includes at least one of conductive carbon black, Ketjen black, acetylene black, and carbon nanotubes.
[0028] In some embodiments, the first binder includes at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0029] In some embodiments, the second conductive agent includes at least one of conductive carbon black, Ketjen black, and acetylene black.
[0030] In some embodiments, the thickener includes at least one of sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), polyvinyl alcohol (PVA), and sodium polyacrylate (PAA-Na).
[0031] In some embodiments, the second binder includes at least one of styrene-butadiene latex (SBR) and polyacrylic acid (PAA).
[0032] In some embodiments, when the active material includes a positive electrode active material, the third binder includes at least one of oil-based polyvinylidene fluoride resin (PVDF), polyacrylic acid (PAA), and polymethyl methacrylate (PMMA).
[0033] In some embodiments, when the active material includes a negative electrode active material, the third binder includes at least one of aqueous polyvinylidene fluoride resin (PVDF), polyacrylic acid (PAA), and polymethyl methacrylate (PMMA).
[0034] In some embodiments, the mass ratio of the ceramic to the binder is (5-9):(5-1).
[0035] In some embodiments, when the active material includes a positive electrode active material, the composite electrode sheet is a positive electrode sheet, and the porosity of the composite electrode sheet is 30-40%.
[0036] In some embodiments, when the active material includes a negative electrode active material, the composite electrode sheet is a negative electrode sheet, and the porosity of the composite electrode sheet is 35-45%.
[0037] In some embodiments, the cohesive force of the composite pole piece is greater than 25 N / m and less than 50 N / m.
[0038] In some embodiments, the thickness of the remaining portion of the first material layer on the current collector is less than 5 μm after a peeling force test, and the peeling force is a N / m, 7<a<30.
[0039] In some embodiments, the surface density of the first material layer is 45-230 g / cm 2 .
[0040] In some embodiments, the surface density of the second material layer is 5-20 g / m 2 .
[0041] In some embodiments, the pore is a micro-nano pore channel, and the diameter of the pore is less than 1 μm.
[0042] In some embodiments, the thermal decomposition temperature is 100-120°C.
[0043] In some embodiments, the current collector includes one of copper foil, aluminum foil, and carbon-coated aluminum foil.
[0044] In some embodiments, the thickness of the first material layer is 50-100 μm.
[0045] In some embodiments, the thickness of the second material layer is 5-20 μm.
[0046] In some embodiments, the mass ratio of the active material to the ceramic is (42.3-223.1):(2.5-18).
[0047] The second aspect of the present application provides a method for preparing a composite pole piece, comprising:
[0048] Using a double-layer coating technology, the first slurry and the second slurry are simultaneously coated on the current collector to form a first coating layer and a second coating layer, respectively, to obtain a current collector containing a slurry layer;
[0049] Drying and rolling the current collector containing the slurry layer to obtain the composite electrode sheet;
[0050] The first slurry includes a material for the first material layer, and the second slurry includes a material for the second material layer.
[0051] In some embodiments, the first slurry further includes a first solvent, and when the active material includes a positive electrode active material, the first solvent includes N-methylpyrrolidone (NMP), or when the active material includes a negative electrode active material, the first solvent includes water.
[0052] In some embodiments, the second slurry further includes a second solvent, and the second solvent includes at least one of water and N-methylpyrrolidone (NMP).
[0053] In some embodiments, when the active material includes a positive electrode active material, the positive electrode active material is lithium iron phosphate, the solid content of the first slurry is 60-64%, and the viscosity of the first slurry is 7000-11000 MPa·s, or, the positive electrode active material is a ternary material, the solid content of the first slurry is 70-74%, and the viscosity of the first slurry is 6000-10000 MPa·s, or, the positive electrode active material is lithium cobalt oxide, the solid content of the first slurry is 76-80%, and the viscosity of the first slurry is 3000-7000 MPa·s.
[0054] In some embodiments, when the active material includes a negative electrode active material, the solid content of the first slurry is 52-56%, and the viscosity of the first slurry is 3000-7000 MPa·s.
[0055] In some embodiments, the solid content of the second slurry is 15-35%, and the viscosity of the second slurry is 3000-7000 MPa·s.
[0056] In some embodiments, the drying temperature is 100-120°C.
[0057] In some embodiments, the pore former is at least partially decomposed to generate gas during the baking process, so that a plurality of pores are formed inside and on the surface of the first coating layer and the second coating layer.
[0058] The third aspect of the present application proposes a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet and / or the negative electrode sheet is a composite electrode sheet described in the present application or a composite electrode sheet prepared by the method for preparing the composite electrode sheet described in the present application.
[0059] A fourth aspect of the present application provides an electrical device, comprising the secondary battery described in the present application.
[0060] The composite pole piece described in this application can at least bring the following beneficial effects:
[0061] A first material layer containing a pore-forming agent and an active substance and a second material layer containing a ceramic with a safety function are sequentially arranged on the surface of the current collector, and both the first material layer and the second material layer contain a plurality of pores, which can improve the safety function and the wettability of the electrode. Specifically, the arrangement of the second material layer containing a ceramic with a safety function can improve the thermal stability of the composite electrode, reduce or even avoid the risk of safety accidents such as fire and explosion caused by internal short circuits of batteries such as lithium batteries; at the same time, since a pore-forming agent is introduced into the first material layer close to the current collector, the pore-forming agent decomposes into gas when heated, and a plurality of pores can be formed inside and on the surface of the first material layer and the second material layer, which improves the porosity of the electrode in situ, thereby improving the wettability of the composite electrode, and effectively improving the risk of reduced wettability caused by the ceramic safety coating.
[0062] The method for preparing the composite electrode described in the present application can at least bring the following beneficial effects:
[0063] The double-layer coating technology shortens the manufacturing process and reduces the manufacturing cost. In addition, the safety ceramic coating (i.e., the second material layer) is processed in situ on the pole piece to improve the probability of lithium dendrites growing and piercing the diaphragm during the charging and discharging process of lithium batteries, causing internal short circuits between the positive and negative electrodes, and leading to safety accidents such as fire and explosion in lithium batteries. At the same time, the introduction of pore-forming agents in the first material layer close to the current collector effectively improves the risk of reduced wettability caused by the ceramic coating covering the active material coating (i.e., the first material layer).
[0064] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0066] in:
[0067] Figure 1 This is a schematic structural diagram of a composite pole piece shown as an exemplary embodiment of the present application.
[0068] Figure 2 The flowchart of a method for preparing a composite pole piece is shown as an exemplary embodiment of the present application, wherein: the active material slurry is also the first slurry, and the ceramic safety coating slurry is also the second slurry.
[0069] Figure 3 This is a scanning electron microscope (SEM) photograph of the composite electrode prepared in Example 1.
[0070] Reference numerals:
[0071] 1-current collector; 2-first material layer; 3-second material layer; 4-hole. DETAILED DESCRIPTION
[0072] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0073] In this application, the disclosure of numerical ranges includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.
[0074] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0075] A composite pole piece and a method for preparing the composite pole piece according to an embodiment of the present application will be described below with reference to the accompanying drawings.
[0076] <Compound Pole Piece>
[0077] Figure 1 This is a schematic structural diagram of a composite pole piece shown as an exemplary embodiment of the present application.
[0078] like Figure 1 As shown, the composite electrode sheet of the embodiment of the present application includes a current collector 1, a first material layer 2 and a second material layer 3. The first material layer 2 is arranged on at least part of the surface of the current collector 1, and the first material layer 2 includes an active material and a pore-forming agent, and the active material includes a positive electrode active material or a negative electrode active material. The second material layer 3 is arranged on at least part of the surface of the first material layer 2, and the second material layer 3 includes ceramics; the second material layer 3 and the first material layer 2 are both provided with a plurality of pores 4 formed by thermal decomposition of at least part of the pore-forming agent.
[0079] It can be understood that in the embodiments of the present application, the current collector, the first material layer and the second material layer are stacked in sequence. When the active material includes a positive electrode active material, the composite electrode sheet is a positive electrode sheet; when the active material includes a negative electrode active material, the composite electrode sheet is a negative electrode sheet. At the same time, the first material layer can be understood as an active material coating because it contains active materials; the second material layer can be understood as a ceramic safety coating or a safety function coating, etc. because it contains ceramics.
[0080] It should be noted that in the embodiments of the present application, multiple holes are formed by thermal decomposition of at least part of the pore-forming agent, wherein thermal decomposition refers to the thermal decomposition of the pore-forming agent during the preparation process of the composite pole piece itself, at least partially forming multiple holes. Specifically, it refers to the preparation process of the composite pole piece itself, after coating the first slurry containing the first material layer (also referred to as the first coating layer hereinafter) and the second slurry containing the second material layer (also referred to as the second coating layer hereinafter) on the current collector, at least part of the pore-forming agent will be thermally decomposed during the drying (also referred to as baking) process to produce CO2, NH3, N2 and other gases, thereby leaving micro-nano pore channels in the internal space of the pole piece - the surface of the pole piece (that is, the interior and surface of the first material layer and the second material layer), that is, multiple of the above-mentioned holes.
[0081] In some embodiments, the pore-forming agent includes but is not limited to at least one of ammonium carbonate, ammonium bicarbonate, azobisisobutyronitrile, benzoyl peroxide, etc. The pore-forming agent is selected from the above substances, which can be thermally decomposed during the processing of the composite pole piece to produce gases such as CO2, NH3, N2, etc., leaving micro-nano pore channels in the internal space of the pole piece-the surface of the pole piece, forming multiple small holes (i.e., holes 4), and the diameter of the small holes is less than 1μm, thereby improving the porosity of the pole piece. In addition, the small holes remaining in the first material layer and the second material layer increase the friction between the first material layer and the second material layer, and enhance the bonding force between the first material layer and the safety coating (second material layer).
[0082] In some embodiments, the particle size of the pore former ranges from 500 nm to 20 μm. In the embodiments of the present application, the particle size of the pore former is within the above range, and a mesoporous structure with effective voids can be obtained, and the infiltration effect is significantly enhanced; if it is less than 500 nm, the pore size is too small, and the effect of improving the wettability may be reduced; if it is greater than 20 μm, the pore size is too large, which may increase the risk of internal short circuits and increase the risk of safety failure.
[0083] Exemplarily, the particle size of the pore-forming agent includes but is not limited to 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm or 20 μm, etc.
[0084] In some embodiments, the median particle size of the pore former is 1-5 μm, including but not limited to 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0085] In some embodiments, the mass content of the pore former in the first material layer is 0.1-3%. In the embodiment of the present application, the mass content of the pore former in the first material layer is within the above range, and the distribution of the pores can be fully controlled; if it is less than 0.1%, the pores are sparsely distributed, and the effect of improving wettability is limited; if it is greater than 3%, the pores are densely distributed, affecting the final quality of the electrode, such as tensile strength, adhesion, etc.
[0086] In some embodiments, the positive electrode active material includes but is not limited to at least one of lithium iron phosphate, ternary materials, lithium cobalt oxide, and the like.
[0087] Exemplary, ternary materials include but are not limited to LiNi x Co y Mn 1-x-y O2 (wherein 0﹤x﹤1, 0﹤y﹤1, 1-xy>0), for example, at least one of NCM111, NCM523, NCM622, NCM811, etc.
[0088] In some embodiments, when the active material includes a positive electrode active material, the material of the first material layer further includes a first conductive agent, a first binder, and the like.
[0089] As an optional example, when the active material includes a positive electrode active material, the material of the first material layer includes the following components in percentage by mass: 94-97% positive electrode active material, 0.5-2% first conductive agent, 1-3% first binder, and 0.1-3% pore former.
[0090] Illustratively, when the active material includes a positive electrode active material, the mass content of the positive electrode active material in the material of the first material layer includes but is not limited to 94%, 95%, 96% or 97%, etc.
[0091] For example, when the active material includes a positive electrode active material, the mass content of the first conductive agent in the material of the first material layer includes, but is not limited to, 0.5%, 1%, 1.5% or 2%.
[0092] Illustratively, when the active material includes a positive electrode active material, the mass content of the first binder in the material of the first material layer includes but is not limited to 1%, 1.5%, 2%, 2.5% or 3%, etc.
[0093] It should be noted that in the embodiments of the present application, when the active material includes a positive electrode active material, the material of the first material layer also includes a first conductive agent, a first binder, etc. The ratio of the positive electrode active material, the first conductive agent, and the first binder is not limited to the above ratio. Since the material of the first material layer is equivalent to the positive electrode material of the positive electrode sheet of the secondary battery in the field, the positive electrode active material, the first conductive agent, and the first binder can also adopt the ratio well known in the field, while ensuring that the mass content of the pore-forming agent is 0.1-3%.
[0094] In some embodiments, the first conductive agent includes, but is not limited to, at least one of conductive carbon black (SP), Ketjen black, acetylene black, carbon nanotubes, and the like.
[0095] In some embodiments, the first binder includes but is not limited to at least one of polyvinylidene fluoride resin (PVDF), polytetrafluoroethylene (PTFE), and the like.
[0096] In some embodiments, the negative electrode active material includes but is not limited to at least one of graphite, silicon-carbon composite materials, silicon-oxygen compounds, silicon, and the like.
[0097] Exemplarily, the silicon-carbon composite material includes but is not limited to at least one of Si / C (mass ratio Si:C=9:1-1:9), etc. Non-limitingly, the mass ratio of Si to C in Si / C is 8:1, 5:1, 3:1, 1:1, 1:2, 1:4, 1:6 or 1:8, etc.
[0098] Exemplary silicon oxide compounds include but are not limited to SiO x , where 1≤x≤2. Non-limiting, SiO x The value of x includes but is not limited to 1.25, 1.5 or 1.75.
[0099] In some embodiments, when the active material includes a negative electrode active material, the material of the first material layer further includes a second conductive agent, a thickener, a second binder, and the like.
[0100] As an optional example, when the active material includes a negative electrode active material, the material of the first material layer includes the following components in percentage by mass: 94-97% negative electrode active material, 0.5-2% second conductive agent, 0.7-2% thickener, 1-2% second binder, and 0.1-3% pore former.
[0101] Illustratively, when the active material includes a negative electrode active material, the mass content of the negative electrode active material in the material of the first material layer includes, but is not limited to, 94%, 95%, 96% or 97%, etc.
[0102] For example, when the active material includes a negative electrode active material, the mass content of the second conductive agent in the material of the first material layer includes, but is not limited to, 0.5%, 1%, 1.5% or 2%.
[0103] For example, when the active material includes a negative electrode active material, the mass content of the thickener in the material of the first material layer includes, but is not limited to, 0.7%, 1%, 1.5% or 2%.
[0104] For example, when the active material includes a negative electrode active material, the mass content of the second binder in the material of the first material layer includes, but is not limited to, 1%, 1.5% or 2%.
[0105] It should be noted that in the embodiments of the present application, when the active material includes a negative electrode active material, the material of the first material layer also includes a second conductive agent, a thickener, a second binder, etc. The ratio of the negative electrode active material, the second conductive agent, the thickener, and the second binder is not limited to the above ratio. Since the material of the first material layer is equivalent to the positive electrode material of the negative electrode plate of the secondary battery in the field, the negative electrode active material, the second conductive agent, the thickener, and the second binder can also be made in a ratio well known in the field, while ensuring that the mass content of the pore-forming agent is 0.1-3%.
[0106] In some embodiments, the material of the second material layer includes ceramic and a third binder.
[0107] In some embodiments, the second conductive agent includes but is not limited to at least one of conductive carbon black (SP), Ketjen black, acetylene black, and the like.
[0108] In some embodiments, the thickener includes but is not limited to at least one of sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), polyvinyl alcohol (PVA), sodium polyacrylate PAA-Na, and the like.
[0109] In some embodiments, the second binder includes but is not limited to at least one of styrene-butadiene latex (SBR), polyacrylic acid (PAA), and the like.
[0110] In some embodiments, the ceramic includes but is not limited to at least one of alumina ceramic, boehmite, etc. In the embodiment of the present application, the ceramic is boehmite, which has low cost, low water absorption and good processing performance.
[0111] In some embodiments, the particle size of the ceramic is in the range of 100 nm to 5 μm. In the embodiments of the present application, the particle size of the ceramic is within the above range, which can improve the processing performance, reduce the difficulty of the processing technology, and ensure the coating quality; if it is less than 100 nm, it is easy to agglomerate, difficult to disperse, and the mechanical properties are reduced; if it is greater than 5 μm, the coating is easy to block the pipe, and the coating thickness and uniformity are difficult to control.
[0112] Exemplarily, the particle size of the ceramic includes but is not limited to 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm, etc.
[0113] In some embodiments, the median particle size of the ceramic is 0.8-1.2 μm, including but not limited to 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, etc., preferably 1 μm.
[0114] In some embodiments, when the active material includes a positive electrode active material, the third binder includes but is not limited to at least one of oil-based polyvinylidene fluoride resin (PVDF), polyacrylic acid (PAA), polymethyl methacrylate (PMMA), and the like.
[0115] In some embodiments, when the active material includes a negative electrode active material, the third binder includes but is not limited to at least one of aqueous polyvinylidene fluoride resin (PVDF), polyacrylic acid (PAA), polymethyl methacrylate (PMMA), and the like.
[0116] In some embodiments, the mass ratio of the ceramic to the binder is (5-9):(5-1), including but not limited to 5:5, 5:4, 5:3, 5:2, 5:1, 6:3, 6:1, 7:1, 7:3, 8:1, 8:3, 8:5 or 9:1, etc.
[0117] In some embodiments, when the active material includes a positive electrode active substance, the composite electrode sheet is a positive electrode sheet, and the porosity of the composite electrode sheet is 30-40%, including but not limited to 30%, 32.5%, 35%, 37.5% or 40%, etc.
[0118] In some embodiments, when the active material includes a negative electrode active material, the composite electrode sheet is a negative electrode sheet, and the porosity of the composite electrode sheet is 35-45%, including but not limited to 35%, 37.5%, 40%, 42.5% or 45%, etc.
[0119] In some embodiments, the cohesive force of the composite pole piece is greater than 25 N / m and less than 50 N / m, including but not limited to 25.5 N / m, 30 N / m, 35 N / m, 40 N / m, 45 N / m or 49.9 N / m, etc.
[0120] In some embodiments, the thickness of the remaining portion of the first material layer on the current collector is less than 5 μm after a peel force test, and the peel force is a N / m, where a is greater than 7.
[0121] As an optional example, 7<a<30. Exemplarily, the value of a includes but is not limited to 7.1, 8, 9, 10, 11, 12, 15, 20, 25 or 29.5. Preferably, when the composite electrode is a positive electrode, 7<a<30; when the composite electrode is a positive electrode, 7<a<25.
[0122] In some embodiments, the surface density of the first material layer is 45-230 g / m 2 , including but not limited to 45g / m 2 , 75g / m 2, 100g / m 2 , 125g / m 2 , 150g / m 2 , 175g / m 2 or 200g / m 2 wait.
[0123] In some embodiments, the surface density of the second material layer is 5-20 g / m 2 , including but not limited to 5g / m 2 , 7.5g / m 2 , 10g / m 2 , 12.5g / m 2 , 15g / m 2 , 17.5g / m 2 or 20g / m 2 wait.
[0124] In the embodiment of the present application, the surface density of the first material layer is less than 45g / cm 2 , the density of the second material layer is less than 5g / cm 2 , which may increase the manufacturing risks in the coating process, such as uneven mass distribution, leakage of dressing foil, etc.; the surface density of the first material layer is greater than 230g / cm 2 , the surface density of the second material layer is greater than 20g / cm 2 , it will increase the risk of negative effects such as uneven surface density distribution and pole piece cracking.
[0125] In some embodiments, the pores are micro-nanopore channels.
[0126] In some embodiments, the diameter of the pore is less than 1 μm, including but not limited to 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 999 nm, etc., preferably 400-800 nm.
[0127] In some embodiments, the temperature of the thermal decomposition is 100-120°C, including but not limited to 100°C, 105°C, 110°C, 115°C or 120°C, etc. As mentioned above, the thermal decomposition here means that at least part of the pore-forming agent is thermally decomposed to produce CO2, NH3, N2 and other gases during the drying stage of the composite electrode preparation process.
[0128] In some embodiments, the current collector includes but is not limited to one of copper foil, aluminum foil, carbon-coated aluminum foil, and the like.
[0129] In some embodiments, the thickness of the first material layer is 50-100 μm.
[0130] In some embodiments, the thickness of the second material layer is 5-20 μm.
[0131] In some embodiments, the mass ratio of the active material to the ceramic is (42.3-223.1): (2.5-18), including but not limited to 42.3:18, 42.3:10, 130:18, 130:2.5 or 130:10, etc. In the embodiments of the present application, the mass ratio of the active material to the ceramic is within the above range, which can maximize the manufacturing reliability of the composite pole piece.
[0132] The composite pole piece of the embodiment of the present application has a first material layer containing a pore-forming agent and an active substance and a second material layer containing a ceramic with a safety function arranged in sequence on the surface of the current collector, and both the first material layer and the second material layer contain a plurality of pores, which can improve the safety function and the wetting performance of the pole piece. Specifically, the provision of the second material layer containing a ceramic with a safety function can improve the thermal stability of the composite pole piece, reduce or even avoid the risk of safety accidents such as fire and explosion caused by internal short circuits of batteries such as lithium batteries; at the same time, since the pore-forming agent is introduced into the first material layer close to the current collector, the pore-forming agent decomposes into gas when heated, and a plurality of pores can be formed inside and on the surface of the first material layer and the second material layer, thereby improving the porosity of the pole piece in situ, thereby improving the wettability of the composite pole piece, and effectively improving the risk of reduced wetting performance caused by the ceramic safety coating.
[0133] <Method for preparing composite pole piece>
[0134] The method for preparing the composite pole piece of the embodiment of the present application can be used to prepare the composite pole piece of the embodiment of the present application.
[0135] Figure 2 The present invention is a flowchart of a method for preparing a composite pole piece according to an exemplary embodiment of the present application.
[0136] like Figure 2 As shown, the preparation method comprises the following steps:
[0137] S101. Using a double-layer coating technology, the first slurry and the second slurry are simultaneously coated on the current collector to form a first coating layer and a second coating layer, respectively, to obtain a current collector containing a slurry layer; the first slurry includes the material of the first material layer, and the second slurry includes the material of the second material layer.
[0138] In some embodiments, the first slurry further comprises a first solvent. At this time, the first slurry can be evenly dispersed by a double planetary mixer.
[0139] Exemplarily, when the active material includes a positive electrode active material, the first solvent includes but is not limited to at least one of N-methylpyrrolidone (NMP), acetone, tetrahydrofuran, and the like.
[0140] As an optional example, when the active material includes a positive electrode active material, the positive electrode active material is lithium iron phosphate, and the solid content of the first slurry is 60-64%, including but not limited to 60%, 61%, 62%, 63% or 64%, etc.; the viscosity of the first slurry is 7000-11000 MPa·s, including but not limited to 7000 MPa·s, 8000 MPa·s, 9000 MPa·s, 10000 MPa·s or 11000 MPa·s, etc.
[0141] As another optional example, when the active material includes a positive electrode active material, the positive electrode active material is a ternary material, and the solid content of the first slurry is 70-74%, including but not limited to 70%, 71%, 72%, 73% or 74%, etc.; the viscosity of the first slurry is 6000-10000 MPa·s, including but not limited to 6000 MPa·s, 7000 MPa·s, 8000 MPa·s, 9000 MPa·s or 10000 MPa·s, etc.
[0142] As another optional example, when the active material includes a positive electrode active material, the positive electrode active material is lithium cobalt oxide, and the solid content of the first slurry is 76-80%, including but not limited to 76%, 77%, 78%, 79% or 80%, etc.; the viscosity of the first slurry is 3000-7000 MPa·s, including but not limited to 3000 MPa·s, 4000 MPa·s, 5000 MPa·s, 6000 MPa·s or 7000 MPa·s, etc.
[0143] Exemplarily, when the active material includes a negative electrode active material, the first solvent includes at least one of water, ethanol, etc., preferably deionized water.
[0144] As an optional example, when the active material includes a negative electrode active material, the solid content of the first slurry is 52-56%, including but not limited to 52%, 53%, 54%, 55% or 56%, etc.; the viscosity of the first slurry is 3000-7000 MPa·s, including but not limited to 3000 MPa·s, 4000 MPa·s, 5000 MPa·s, 6000 MPa·s or 7000 MPa·s, etc.
[0145] In some embodiments, the second slurry further comprises a second solvent. At this time, the second slurry can be evenly dispersed by a double planetary mixer.
[0146] In some embodiments, the second solvent includes but is not limited to at least one of water, N-methylpyrrolidone (NMP), and the like.
[0147] As an optional example, when the active material includes a positive electrode active material, the second solvent is N-methylpyrrolidone (NMP), and the third binder is oil-based PVDF.
[0148] As another optional example, when the active material includes a negative electrode active material, the second solvent is deionized water, and the third binder is aqueous PVDF.
[0149] In some embodiments, the solid content of the second slurry is 15-35%, including but not limited to 15%, 20%, 25%, 30% or 35%, etc.
[0150] In some embodiments, the viscosity of the second slurry is 3000-7000 MPa·s, including but not limited to 3000 MPa·s, 4000 MPa·s, 5000 MPa·s, 6000 MPa·s or 7000 MPa·s.
[0151] As an optional example, a double-layer coating technology is used to simultaneously coat the first slurry and the second slurry on the current collector to form a first coating layer and a second coating layer, respectively, to obtain a current collector containing a slurry layer, including:
[0152] The first slurry and the second slurry are pumped into the two chambers of the double-layer coating die head respectively through the feeding system of the double-layer coating machine, and a current collector containing a slurry layer is prepared through the double-layer coating technology.
[0153] S102, drying and rolling the current collector containing the slurry layer to obtain the composite electrode sheet.
[0154] In some embodiments, the drying temperature is 100-120°C, including but not limited to 100°C, 105°C, 110°C, 115°C or 120°C, etc.
[0155] In the embodiments of the present application, drying is also referred to as baking in some cases.
[0156] In some embodiments, the pore former is at least partially decomposed to generate gas during the baking process, so that a plurality of pores are formed inside and on the surface of the first coating layer and the second coating layer.
[0157] Exemplarily, the pore former at least partially decomposes during the baking process to produce gases such as CO2, NH3, N2, etc.
[0158] In the embodiment of the present application, during the drying process, the pore-forming agent in the first slurry realizes the pore-forming effect. The specific pore-forming principle is: since the pore-forming agent decomposes at 100-120°C in the drying stage to produce gases such as CO2, NH3, and N2, a micro-nano pore channel (i.e., hole 4) is left in the internal space of the electrode-the surface of the electrode (i.e., the first coating layer and the second coating layer, corresponding to the first material layer and the second material layer in the composite electrode), and the pore diameter is less than 1μm, thereby improving the porosity of the electrode. In addition, the small holes remaining in the first coating layer and the second coating layer increase the friction between the first coating layer and the second coating layer, and enhance the bonding force between the first coating layer and the safety coating (the second coating layer).
[0159] The preparation method of the composite pole piece of the embodiment of the present application shortens the manufacturing process and reduces the manufacturing cost through double-layer coating technology. In addition, the safety ceramic coating (i.e., the second material layer) is obtained by in-situ processing on the pole piece, which improves the probability of lithium dendrite growth, piercing the diaphragm, causing internal short circuits between the positive and negative electrodes in direct contact during the charging and discharging process of lithium batteries and other batteries, and causing fires, explosions and other safety accidents in lithium batteries. At the same time, the introduction of a pore-forming agent in the first material layer close to the current collector effectively improves the risk of reduced wettability caused by the ceramic coating covering the active material coating (i.e., the first material layer).
[0160] <Secondary Battery>
[0161] The secondary battery of the embodiment of the present application comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet and / or the negative electrode sheet is a composite electrode sheet of the embodiment of the present application or a composite electrode sheet prepared by the method for preparing the composite electrode sheet of the embodiment of the present application.
[0162] It can be understood that, in the composite electrode sheet of the embodiment of the present application, when the active material in the material of the first material layer includes a positive electrode active material, the composite electrode sheet is a positive electrode sheet; when the active material in the material of the first material layer includes a negative electrode active material, the composite electrode sheet is a negative electrode sheet. Therefore, in the secondary battery of the embodiment of the present application, the positive electrode sheet can adopt the composite electrode sheet of the embodiment of the present application as the positive electrode sheet, and the negative electrode sheet can adopt the composite electrode sheet of the embodiment of the present application as the negative electrode sheet. It is also possible to prepare the composite electrode sheet of the embodiment of the present application as the positive electrode sheet and the composite electrode sheet as the negative electrode sheet separately, and use them both in the secondary battery of the embodiment of the present application.
[0163] It should be noted that, according to the different types of active materials in the first material layer of the composite electrode in the embodiment of the present application, the above-mentioned secondary battery may be a different secondary battery, such as a lithium ion battery, a sodium ion battery, a potassium ion battery, etc.
[0164] As a preferred example, the secondary battery in the embodiment of the present application is a lithium-ion battery.
[0165] <Electrical Devices>
[0166] The electric device according to the embodiment of the present application includes the secondary battery according to the embodiment of the present application.
[0167] In some embodiments, the above-mentioned power-consuming devices include but are not limited to mobile phones, tablet computers, new energy vehicles, etc.
[0168] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0169] 1. Examples and Comparative Examples
[0170] Example 1 (Negative Electrode Plate)
[0171] (Preparation of composite pole piece)
[0172] The composite electrode sheet of this embodiment is a negative electrode sheet, and its preparation method includes the following steps:
[0173] (1) Preparing a first slurry: adding the material of the first material layer into a first solvent, deionized water, and dispersing the material evenly by a double planetary mixer to obtain a first slurry with a solid content of 52%±2% and a viscosity of 5000±2000 MP·s.
[0174] The material of the first material layer is composed of the following components in mass percentage: 96.3% graphite, 0.8% carbon black, 1.2% CMC-Na, 1.6% SBR, and 0.1% ammonium carbonate. The particle size of the ammonium carbonate ranges from 500nm to 2μm, and the median particle size is 1μm.
[0175] (2) Preparing a second slurry: adding the material of the second material layer into the second solvent deionized water, and dispersing them evenly by a double planetary mixer to obtain a first slurry with a solid content of 20%±2% and a viscosity of 800±200 MP·s.
[0176] The material of the second material layer is composed of the following components in mass percentage: 80% Al2O3 ceramics, 20% water-based PVDF. The particle size of the Al2O3 ceramics ranges from 500nm to 1.4μm, and the median particle size is 0.9μm.
[0177] (3) Using a double-layer coating technology, the first slurry obtained in step (1) is set as a slurry close to the current collector, and the second slurry obtained in step (2) is set as a slurry close to the first slurry but away from the current collector. The two slurries are simultaneously coated on the current collector by a double-layer coating machine. The first slurry is coated to form a first coating layer, and the second slurry is coated to form a second coating layer. The first coating layer is arranged on one surface of the current collector, and the second coating layer is arranged on the surface of the first coating layer. The current collector, the first coating layer, and the second coating layer are stacked in sequence to obtain a current collector containing a slurry layer.
[0178] The current collector is made of copper foil with a thickness of 6 μm; the surface density (single side) of the first coating layer is 95 g / m 2 , the second coating layer density (single side) is 10g / m 2 .
[0179] (4) The current collector containing the slurry layer obtained in step (3) is dried at 120°C, and the ammonium carbonate is decomposed to produce CO2 and NH3, and a plurality of holes are formed inside and on the surface of the first coating layer and the second coating layer. After that, the first coating layer is rolled to become the first material layer, and the second coating layer is rolled to become the second material layer, thereby obtaining a composite electrode sheet with improved safety performance of the lithium battery, i.e., the composite electrode sheet of this embodiment.
[0180] Example 2 (positive electrode plate, positive electrode active material is lithium iron phosphate)
[0181] This embodiment is basically the same as Embodiment 1, except that:
[0182] The composite electrode of this embodiment is a positive electrode. In step (1), the material of the first material layer is added to the first solvent NMP, and is evenly dispersed by a double planetary mixer to obtain a first slurry with a solid content of 62% ± 2% and a viscosity of 9000 ± 2000 MP·s. The material of the first material layer is composed of the following components in mass percentage: 95.5% lithium iron phosphate material, 1.5% SP, 2% PVDF, and 1% azobisisobutyronitrile. The particle size range of azobisisobutyronitrile is 800nm-5μm, and the median particle size is 2μm.
[0183] In step (2), among the materials of the second material layer, the PVDF is oil-based PVDF.
[0184] In step (3), the current collector is made of aluminum foil with a thickness of 13 μm.
[0185] In step (4), the drying temperature is 100° C., and azobisisobutyronitrile decomposes to produce N 2 , forming a plurality of pores inside and on the surface of the first coating layer and the second coating layer.
[0186] Example 3 (positive electrode sheet, positive electrode active material is ternary material)
[0187] This embodiment is basically the same as Embodiment 1, except that:
[0188] The composite electrode sheet of this embodiment is a positive electrode sheet. In step (1), the material of the first material layer is added to the first solvent NMP and dispersed evenly by a double planetary mixer to obtain a first slurry with a solid content of 72%±2% and a viscosity of 9000±2000MP·s. The material of the first material layer is composed of the following components in mass percentage: 95.5% ternary positive electrode material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 02), 1.5% SP, 2% PVDF, 1% azobisisobutyronitrile. The particle size of azobisisobutyronitrile ranges from 800nm to 5μm, and the median particle size is 2μm.
[0189] In step (2), among the materials of the second material layer, the PVDF is oil-based PVDF.
[0190] In step (3), the current collector is made of aluminum foil with a thickness of 13 μm.
[0191] In step (4), the drying temperature is 100° C., and azobisisobutyronitrile decomposes to produce N 2 , forming a plurality of pores inside and on the surface of the first coating layer and the second coating layer.
[0192] Example 4 (ceramic content in ceramic slurry is 90% of the upper limit)
[0193] This embodiment is basically the same as Embodiment 1, except that:
[0194] In step (2), the material of the second material layer is composed of the following components in mass percentage: 90% Al2O3 ceramic and 10% PVDF.
[0195] Example 5 (ceramic content in ceramic slurry is 70%)
[0196] This embodiment is basically the same as Embodiment 1, except that:
[0197] In step (2), the material of the second material layer is composed of the following components in mass percentage: 70% Al2O3 ceramic and 30% PVDF.
[0198] Example 6 (ceramic content in ceramic slurry is 60%)
[0199] This embodiment is basically the same as Embodiment 1, except that:
[0200] In step (2), the material of the second material layer is composed of the following components in mass percentage: 60% Al2O3 ceramic and 40% PVDF.
[0201] Example 7 (ceramic content in ceramic slurry is 50% lower limit)
[0202] This embodiment is basically the same as Embodiment 1, except that:
[0203] In step (2), the material of the second material layer is composed of the following components in the following mass percentages: 50% Al2O3 ceramics and 50% PVDF.
[0204] Example 8 (lower limit of density of the second coating layer 5g / m 2 )
[0205] This embodiment is basically the same as Embodiment 1, except that:
[0206] In step (3), the second coating layer density (single side) is 5g / m 2 .
[0207] Example 9 (second coating layer density middle 8g / m 2 )
[0208] This embodiment is basically the same as Embodiment 1, except that:
[0209] In step (3), the second coating layer density (single side) is 8g / m 2 .
[0210] Example 10 (second coating layer density middle 13g / m 2 )
[0211] This embodiment is basically the same as Embodiment 1, except that:
[0212] In step (3), the second coating layer density (single side) is 13g / m 2 .
[0213] Example 11 (second coating layer density middle 15g / m 2 )
[0214] This embodiment is basically the same as Embodiment 1, except that:
[0215] In step (3), the second coating layer density (single side) is 15g / m 2 .
[0216] Example 12 (upper limit of density of the second coating layer 20g / m 2 )
[0217] This embodiment is basically the same as Embodiment 1, except that:
[0218] In step (3), the second coating layer density (single side) is 20g / m 2 .
[0219] Example 13 (Compared with Example 1, the pore-forming agent is benzoyl peroxide)
[0220] This embodiment is basically the same as Embodiment 1, except that:
[0221] In step (1), ammonium carbonate is replaced by benzoyl peroxide; the particle size of benzoyl peroxide ranges from 1 μm to 10 μm, and the median particle size is 4 μm.
[0222] In step (4), the drying temperature is 120° C., and benzoyl peroxide decomposes to produce CO 2 , forming a plurality of pores inside and on the surface of the first coating layer and the second coating layer.
[0223] Example 14 (Compared with Example 1, the pore-forming agent is a 1:1 mixture of ammonium bicarbonate and azobisisobutyronitrile)
[0224] This embodiment is basically the same as Embodiment 1, except that:
[0225] In step (1), ammonium carbonate is replaced by a mixture of ammonium bicarbonate and benzoyl peroxide in a mass ratio of 1:1; the particle size range of ammonium bicarbonate is 1-20 μm, and the median particle size is 5 μm; the particle size range of benzoyl peroxide is 1 μm-10 μm, and the median particle size is 4 μm.
[0226] In step (4), the drying temperature is 120° C., ammonium bicarbonate decomposes to produce CO 2 and NH 3 , and azobisisobutyronitrile decomposes to produce N 2 , forming a plurality of pores inside and on the surface of the first coating layer and the second coating layer.
[0227] Example 15 (Compared with Example 2, the pore-forming agent is benzoyl peroxide)
[0228] This embodiment is basically the same as Embodiment 2, except that:
[0229] In step (1), azobisisobutyronitrile is replaced by benzoyl peroxide; the particle size range of benzoyl peroxide is 1-10, and the median particle size is 4 μm.
[0230] In step (4), the drying temperature is 120° C., and benzoyl peroxide decomposes to produce CO 2 , forming a plurality of pores inside and on the surface of the first coating layer and the second coating layer.
[0231] Example 16 (Compared with Example 1, the pore-forming agent content is 1.55%)
[0232] This embodiment is basically the same as Embodiment 1, except that:
[0233] In step (1), the material of the first material layer is composed of the following components in mass percentage: 95% graphite, 0.8% carbon black, 1.15% CMC, 1.5% SBR, and 1.55% ammonium carbonate.
[0234] Example 17 (Compared with Example 1, the pore-forming agent content is the upper limit of 3%)
[0235] This embodiment is basically the same as Embodiment 1, except that:
[0236] In step (1), the material of the first material layer is composed of the following components in mass percentage: 94.35% graphite, 0.5% carbon black, 1.15% CMC, 1% SBR, and 3% ammonium carbonate.
[0237] Example 18 (Compared with Example 2, the pore-forming agent content is the lower limit 0.1%)
[0238] This embodiment is basically the same as Embodiment 1, except that:
[0239] In step (1), the material of the first material layer is composed of the following components in mass percentage: 97% lithium iron phosphate, 1.5% SP, 1.4% PVDF, and 0.1% azobisisobutyronitrile.
[0240] Example 19 (Compared with Example 2, the pore-forming agent content is 1.55%)
[0241] In step (1), the material of the first material layer is composed of the following components in mass percentage: 94.95% lithium iron phosphate, 1.5% SP, 2% PVDF, and 1.55% azobisisobutyronitrile.
[0242] Example 20 (Compared with Example 2, the pore-forming agent content is the upper limit of 3%)
[0243] In step (1), the material of the first material layer is composed of the following components in mass percentage: 94% lithium iron phosphate, 1.5% SP, 1.5% PVDF, and 3% azobisisobutyronitrile.
[0244] Example 21 (Compared with Example 1, the ceramic is boehmite)
[0245] This embodiment is basically the same as Embodiment 1, except that:
[0246] In step (2), the Al2O3 ceramic is replaced by boehmite.
[0247] Comparative Example 1
[0248] This comparative example provides a method for preparing a negative electrode sheet, and the specific preparation process is as follows:
[0249] Step 1: Add deionized water to graphite, carbon black, SBR and CMC in a mass ratio of 96.4:0.8:1.6:1.2 to prepare a slurry with a solid content of 52%±4%, a viscosity of 3000-7000mPa·s and a slurry fineness of less than 35μm.
[0250] Step 2: Use an extrusion coater to evenly coat the slurry prepared in step 1 on a 6μm copper foil. Adjust the coater and dry it to obtain a (single-sided) surface density of 95g / m 2 A negative electrode sheet with a current collector.
[0251] Comparative Example 2
[0252] This comparative example provides a method for preparing a positive electrode sheet, and the specific preparation process is as follows:
[0253] Step 1: Add NMP to lithium iron phosphate material, SP, and PVDF in a mass ratio of 96.5%:1.5%:2% to prepare a slurry with a solid content of 62%±4%, a viscosity of 7000-11000mPa·s, and a slurry fineness of less than 35μm.
[0254] Step 2: Use an extrusion coater to evenly coat the slurry prepared in step 1 on a 13 μm carbon-coated aluminum foil. Adjust the coater and dry it to obtain a (single-sided) surface density of 210 g / m 2 A positive electrode sheet with a current collector.
[0255] Comparative Example 3
[0256] This comparative example provides a method for preparing a positive electrode sheet, and the specific preparation process is as follows:
[0257] Step 1: Add deionized water to the ternary material (NCM811), SP, and PVDF in a mass ratio of 96.5%:1.5%:2% to prepare a slurry with a solid content of 72%±4%, a viscosity of 7000-11000mPa·s, and a slurry fineness of <35μm and uniform dispersion.
[0258] Step 2: Use an extrusion coater to evenly coat the slurry prepared in step 1 on a 13 μm carbon-coated aluminum foil. Adjust the coater and dry it to obtain a (single-sided) surface density of 160 g / m 2 A positive electrode sheet with a current collector.
[0259] Comparative Example 4
[0260] This comparative example is basically the same as Example 1, except that the addition of the pore-forming agent ammonium carbonate in step (1) is omitted.
[0261] In step (1), the material of the first material layer is composed of the following components in percentage by mass: 96.4% graphite, 0.8% carbon black, 1.2% CMC, and 1.6% SBR.
[0262] Comparative Example 5
[0263] This comparative example is basically the same as Example 2, except that the addition of the pore-forming agent azobisisobutyronitrile in step (1) is omitted.
[0264] In step (1), the material of the first material layer is composed of the following components in mass percentage: 96.5% lithium iron phosphate material, 1.5% SP, and 2% PVDF.
[0265] Comparative Example 6
[0266] This comparative example is basically the same as Example 3, except that the addition of the pore-forming agent azobisisobutyronitrile in step (1) is omitted.
[0267] In step (1), the material of the first material layer is composed of the following components in mass percentage: 96.5% ternary positive electrode material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 02), 1.5% SP, 2% PVDF.
[0268] 2. Pole Characterization and Performance Testing
[0269] 1. Pole characterization and performance testing
[0270] (1) Pole characterization
[0271] The morphology of the electrode pieces of each embodiment or comparative example was tested by scanning electron microscopy (SEM), wherein the SEM electron microscope photograph of the composite electrode piece prepared in Example 1 is as follows: Figure 3 As shown. Figure 3 It can be seen that there are multiple holes in the composite pole piece.
[0272] (2) Pole piece porosity test
[0273] The electrode porosity test method is as follows: take the electrode prepared in each embodiment or comparative example, and use a roller press to prepare different compaction electrode sheets according to the type of active material in the first coating layer. After rolling, the electrode sheets (graphite, lithium iron phosphate, and ternary material compaction are 1.6 g / cm 3 , 2.5g / cm 3 and 3.4 g / cm 3 ). Use a punching machine to cut the rolled negative electrode sheet into 100 small discs with a diameter of 14 mm. Use a digital micrometer to measure the thickness of the small discs. Place the sample to be tested in a fully automatic true density tester and use the formula: V = πR2 hN is the sample volume, where R is the disc radius (in mm), h is the disc thickness (in mm), N is the number of discs (in pieces), and V is the sample volume (in cm 3 ), after all parameters of the true density test are set, select the porosity test, start the test, and obtain the electrode porosity.
[0274] (3) Pole cohesion test
[0275] The test method of the pole piece cohesion test is as follows: take the pole piece prepared in each embodiment or comparative example, and use a roller press to prepare pole pieces with different compactions according to the type of active material in the first coating layer. After rolling, the pole piece (the compaction of graphite, lithium iron phosphate, and ternary material is 1.6 g / cm 3 , 2.5g / cm 3 and 3.4 g / cm 3 ). Cut the rolled electrode into 2.5cm×25cm strips, stick the double-sided adhesive tape on the steel plate, and use the roller to go back and forth 3 times to make the double-sided adhesive tape and the steel plate stick tightly; then, stick another layer of green glue on the negative electrode, clamp the green glue on the tensile machine and peel it 180°, peel off the coating layer-dressing layer, read the data, and get the cohesion.
[0276] (4) Pole peeling force test
[0277] The test method of the pole piece peeling force test is as follows: take the pole pieces prepared in each embodiment or comparative example, and prepare them into pole pieces with different compaction according to the type of active material in the first coating layer (the compaction of graphite, lithium iron phosphate, and ternary material is 1.6 g / cm 3 , 2.5g / cm 3 and 3.4 g / cm 3 ). Cut the rolled electrode into 2.5cm×25cm strips, stick the double-sided adhesive tape on the steel plate, and roll back and forth 3 times to make the double-sided adhesive tape and the steel plate stick tightly; then stick the cut electrode strips to the steel plate through the double-sided adhesive tape, and roll back and forth 3 times to make them stick tightly; fix the steel plate on the peeling tester, so that the electrode and the peeling direction are always controlled at 180°, perform the peeling force test, read the data, and obtain the peeling force.
[0278] (5) Pole DSC thermal stability test
[0279] The method for testing the thermal stability of the pole piece by DSC is as follows: the powder of the pole piece prepared in each embodiment or comparative example is scraped off, and the thermal stability (decomposition temperature) of the pole piece composite coating is tested by differential scanning calorimetry (DSC). The test temperature range is: 45°C-500°C.
[0280] 2. Safety performance and electrochemical performance test
[0281] Battery preparation:
[0282] Preparation of Battery 1: The positive electrode sheet prepared in each embodiment or comparative example, the commercial negative electrode sheet (graphite system), and the separator are prepared into Battery 1. The specific preparation method includes the following steps:
[0283] 1) Preparation of commercial negative electrode sheet (graphite system): the same preparation method of the negative electrode sheet as that of Comparative Example 1.
[0284] 2) Preparation of electrolyte: EC / EMC / DMC=30wt%:40wt%:30wt%, 0.5M LiPF6+0.5MLiFSI, 2.5%wtVC, 0.5%wtFEC, 0.5wt%DTD. EC is ethylene carbonate, EMC is ethyl methyl carbonate, DMC is dimethyl carbonate, LiPF6 is lithium hexafluorophosphate, LiFSI is lithium bis(fluorosulfonyl)imide, VC is vinylene carbonate, FEC is fluoroethylene carbonate, and DTD is vinyl sulfate.
[0285] 3) Selection of diaphragm: 9μm PE single-sided glue-coated diaphragm.
[0286] 4) Assembly: The positive electrode sheet, separator and negative electrode sheet prepared in each embodiment or comparative example are assembled according to an NP ratio or CB value (ratio of negative electrode surface capacity to positive electrode surface capacity) of ≥1.05, followed by liquid injection, and then prepared into a square aluminum shell battery through battery manufacturing processes such as packaging, formation, and capacity division.
[0287] Preparation of Battery 2: The negative electrode sheet prepared in each embodiment or comparative example and the commercial positive electrode sheet (ternary 811 system or lithium iron phosphate system) and the separator are prepared into Battery 2 (Note: The battery 2 shown in this application is lithium iron phosphate-graphite or NCM811-graphite system, but is not limited to these two systems in practical applications). The specific preparation method includes the following steps:
[0288] 1) Preparation of commercial positive electrode sheets: the preparation method of the positive electrode sheet of the ternary 811 system is the same as that of Comparative Example 3; the preparation method of the positive electrode sheet of the lithium iron phosphate system is the same as that of Comparative Example 2.
[0289] 2) Preparation of electrolyte: EC / EMC / DMC=30wt%:40wt%:30wt%, 0.8M LiPF6+0.25MLiFSI, 2.5%wtVC, 0.5%wtFEC, 0.5wt%DTD. EC is ethylene carbonate, EMC is ethyl methyl carbonate, DMC is dimethyl carbonate, LiPF6 is lithium hexafluorophosphate, LiFSI is bis(fluorosulfonyl)imide lithium salt, VC is vinylene carbonate, FEC is fluoroethylene carbonate, and DTD is vinyl sulfate.
[0290] 3) Selection of diaphragm: 9μm PE single-sided glue-coated diaphragm.
[0291] 4) Assembly: Assemble the positive electrode sheet, the separator and the negative electrode sheet prepared in each embodiment or comparative example, then inject liquid, and then go through battery manufacturing processes such as packaging, formation, and capacity division to prepare a square aluminum shell battery.
[0292] The safety performance and electrochemical performance of the battery 1 or battery 2 corresponding to the composite electrode prepared in each embodiment or comparative example were tested.
[0293] (1) Safety performance test involves overcharge test and needle penetration test. Among them:
[0294] The overcharge test method is: charge the aluminum shell battery at 0.33C to the cut-off voltage (voltage window of lithium iron phosphate-graphite system: 2.5-3.65V; voltage window of ternary NCM811-graphite system: 2.8-4.2V), and then charge at constant voltage until the current drops to 0.05C. Let it stand for 2 hours, then charge at 1C to 1.5 times the voltage or stop charging after charging for 30 minutes. Observe whether thermal runaway occurs. If it does, record the state of charge (SOC) when thermal runaway occurs.
[0295] The method of needle puncture test is: charge the aluminum shell battery at 0.33C to the cut-off voltage (voltage window of lithium iron phosphate graphite system: 2.5-3.65V; voltage window of ternary NCM811 graphite system: 2.8-4.2V), and then charge at constant voltage until the current drops to 0.05C. Use a φ5mm high temperature resistant steel needle (the cone angle of the steel needle is 55°, the surface is smooth, without rust, oxide layer and oil stains), and penetrate it from the direction perpendicular to the battery plate at a speed of (25) mm / s. The penetration position should be close to the geometric center of the punctured surface. The steel needle stays in the battery and is observed for 1 hour after completion.
[0296] (2) Test of electrochemical performance
[0297] Cycle test method: Place the prepared square aluminum shell battery in a 25℃ room temperature environment, charge at 1 / 3C, and discharge at 1C for cycling. The specific operation steps are: stand for 1h, charge at 1 / 3C constant current to Umax, continue constant voltage charging until the current is less than 0.05C and then cut off; stand for 1h, discharge at 1C constant current to Umin; stand for 1h, the above is a charge and discharge cycle of the battery, repeat the above cycle until the battery capacity decays to 80% of the initial value, and record the number of cycles. (Note: LiFePO4-graphite system, Umax=3.65V, Umin=2.5V, NCM811-graphite system, Umax=4.2V, Umin=2.8V).
[0298] Rate charging test method: Place the prepared square aluminum shell battery in a 25℃ room temperature environment, let it stand for 2h, charge it to Umax at 3C, continue to charge at constant voltage until the current is less than 0.05C, then stop, let it stand for 1h, discharge it to Umin at 1C constant current, and repeat the above steps 3 times. The ratio of the third 3C charging capacity to the rated capacity is recorded as the rate charging retention rate. Note: The rated capacity is the capacity discharged at 1C constant current to Umin at a temperature of 25℃. When the positive electrode is iron lithium and the negative electrode is graphite, Umax = 3.65V, Umin = 2.5V. When the positive electrode is NCM811 and the negative electrode is graphite, Umax = 4.2V, Umin = 2.8V).
[0299] The DSC thermal stability and safety performance test results of the above-mentioned electrode are shown in Table 1, the electrode porosity, cohesion and peeling force test results are shown in Table 2, and the electrochemical performance test results are shown in Table 3.
[0300] Table 1 DSC thermal stability and safety performance test results of the pole piece
[0301]
[0302]
[0303] As shown in Table 1:
[0304] By comparing Examples 1-3 and Comparative Examples 1-3, it is not difficult to find that under the same active material, the decomposition temperature of the composite electrode provided in the present application is higher than the decomposition temperature of the conventional electrode, which will be beneficial to improving the thermal stability of the battery cell and improving safety.
[0305] By comparing Examples 1-3, we can find that the present application provides a method for preparing a composite pole piece, and the prepared batteries of Examples 1-3 all passed the puncture test. In Example 3, since the positive electrode adopts the ternary material NCM811, thermal runaway occurred during overcharging, but its SOC when overcharging thermal runaway occurred was 142.1%, which was much higher than 113.2% of Comparative Example 3, which increased the difficulty of thermal runaway and improved safety. In addition, Comparative Examples 1-3 all failed the puncture test, indicating that compared with the pole piece preparation methods of Comparative Examples 1-3, the method provided by the present application can effectively improve the safety performance of the battery cell.
[0306] By comparing Example 1 with Examples 4-7, we found that as the ceramic content in the second slurry decreases, the ceramic content in the ceramic coating (i.e., the second material layer) decreases, and the risk of overcharge thermal runaway gradually increases. When the mass ratio of ceramic to binder (i.e., the third binder) is reduced to 6:4, overcharge thermal runaway occurs, and the failure SOC is 135.4%. Despite this, it is still higher than the 114.5% SOC of the comparative example 1 without ceramic coating when overcharge thermal runaway failure occurs.
[0307] Comparing Example 1 with Examples 8-12, we found that as the density (thickness) of the second coating layer gradually decreased, the risk of thermal runaway gradually increased. When the density of the second coating layer was reduced to 5 g / m 2 , it failed due to overcharge, and the failure SOC was 137.8%, which was much higher than the charge state of 114.5% SOC at which failure occurred in comparative example 1.
[0308] It can be seen from Example 1 and Examples 13-14, Comparative Example 2 and Example 15 that when the prepared composite electrode is a negative electrode, changing the type of pore former within the scope specified in the present application has little effect on the thermal stability and safety performance of the DSC; when the prepared composite electrode is a positive electrode, changing the type of pore former within the scope specified in the present application will change the decomposition temperature. The specific pore former benzoyl peroxide has a higher decomposition temperature than azobisisobutyronitrile, but the change of the pore former does not affect the passing of the needle puncture test, and thermal runaway will not occur due to overcharging.
[0309] By comparing Example 1 with Examples 16-17, and by comparing Example 2 with Examples 18-20, it can be seen that when the prepared composite electrode sheet is a negative electrode sheet, within the range specified in the present application, as the content of the pore-forming agent increases, the DSC thermal stability and safety performance do not differ much, but when the content of the pore-forming agent is the upper limit of 3%, the thermal decomposition temperature will decrease; when the prepared composite electrode sheet is a positive electrode sheet, within the range specified in the present application, as the content of the pore-forming agent increases, the decomposition temperature gradually decreases, but all can pass the needle puncture test, and thermal runaway will not occur.
[0310] By comparing Example 1 and Example 21, it can be seen that, within the scope defined in the present application, changing the type of ceramic has no effect on the thermal stability and safety performance of DSC.
[0311] It can be seen from Comparative Example 1 and Comparative Example 4, Comparative Example 2 and Comparative Example 5, Comparative Example 3 and Comparative Example 6 that the DSC thermal stability and safety performance of Example 1 and Comparative Example 4, Comparative Example 2 and Comparative Example 5, Comparative Example 3 and Comparative Example 6 of the present application are basically equivalent.
[0312] Table 2. Test results of electrode porosity, cohesion and peeling force
[0313]
[0314]
[0315] As shown in Table 2:
[0316] By comparing Examples 1-3 and Comparative Examples 4-6, it is not difficult to find that the porosity of the composite pole piece prepared by the present application is higher than that of the pole piece of the same first coating layer type, among which the porosity of the graphite negative pole piece is increased from 36.1% to 40.3%, the porosity of the lithium iron phosphate positive pole piece is increased from 31.3% to 35.2%, and the porosity of the ternary material NCM811 positive pole piece is increased from 33.4% to 37.4%. This shows that the present application can effectively improve the porosity of the pole piece. In addition, its cohesion is also correspondingly improved, which is mainly because the pore-making channel increases the friction between the first material layer and the second material layer, and indirectly improves the cohesion of the pole piece. The increase in the peeling force is not large, indicating that there is no obvious effect on the bonding effect at the current collector. Therefore, the composite pole piece and its preparation method provided by the present application can improve the pole piece porosity without weakening the peeling force, while also having a safety function.
[0317] By comparing Example 1 with Examples 4-7, it can be seen that as the ceramic content in the second slurry decreases, the ceramic content in the ceramic coating (ie, the second material layer) decreases, the porosity of the composite electrode gradually decreases, and the cohesion and peeling force gradually increase.
[0318] By comparing Example 1 with Examples 8-12, it can be seen that as the density (thickness) of the second coating layer gradually decreases, the porosity of the composite electrode gradually increases, and the cohesive force and the peeling force gradually decrease.
[0319] For Example 1 and Example 13-14, Comparative Example 2 and Example 15, it can be seen that the porosity of the composite pole piece is different when different pore-forming agents are used, which leads to differences in cohesion and peeling force, but they are all within the scope defined in this application. Specifically: When the composite pole piece is a negative pole piece, under the same conditions, the pore-forming agent is a 1:1 mixture of ammonium bicarbonate and azobisisobutyronitrile, benzoyl peroxide and ammonium carbonate, the porosity of the composite pole piece gradually decreases, and the cohesion and peeling force also gradually decrease. This is mainly because the pore-forming channel increases the friction between the first material layer and the second material layer, and the friction between the first material layer and the current collector, which indirectly increases the cohesion of the pole piece, the bonding force between the first material layer and the second material layer, and the bonding force between the first material layer and the current collector. The higher the porosity, the higher the cohesion and peeling force of the pole piece. When the composite pole piece is a positive pole piece, under the same conditions, the pore-forming agent using benzoyl peroxide can obtain higher porosity, cohesion and peeling force than azobisisobutyronitrile.
[0320] By comparing Example 1 with Examples 16-17, and by comparing Example 2 with Examples 18-20, it can be seen that within the range specified in the present application, as the content of the pore-forming agent increases, the porosity of the composite electrode gradually increases, and the cohesion and peeling force both first increase and then decrease, indicating that the pore-forming agent content of the present application has an optimal value within the specified range. At this time, the porosity obtained is moderate, and the cohesion and peeling force are the highest. However, if the optimal value is exceeded, the porosity will be further improved. However, due to the excessively high porosity, the cohesion and peeling force may be reduced (but the higher the porosity, the better the wettability of the electrolyte, and thus better battery electrochemical performance can be obtained, as shown in Table 3 below for electrochemical performance test results).
[0321] By comparing Example 1 and Example 21, it can be seen that, within the range defined in the present application, changing the type of ceramic has substantially no effect on the porosity, cohesion and peeling force.
[0322] By comparing Examples 1-3 and Comparative Examples 1-3, it can be seen that under the same active material, the composite electrode of the present application has higher porosity, cohesion and peeling force due to the presence of a pore-forming agent and a second material layer.
[0323] Table 3 Electrochemical performance test results
[0324]
[0325]
[0326] From Table 3 we can see that:
[0327] By comparing Examples 1-3 and Comparative Examples 4-6, it can be seen that the battery assembled with the composite pole piece prepared in the present application has better electrochemical performance. This may be because the composite pole piece prepared in the present application has a higher porosity, and the high porosity can improve the wettability of the electrolyte, thereby improving the electrochemical performance of the battery such as the cycle capacity retention rate and the rate charging capacity retention rate.
[0328] By comparing Example 1 with Examples 4-7, it can be seen that as the ceramic content in the second slurry decreases, the ceramic content in the ceramic coating (i.e., the second material layer) decreases, and the cycle capacity retention rate and rate charge capacity retention rate of the battery gradually decrease. This may be due to the gradual decrease in the porosity of the composite electrode, which causes the wettability of the electrolyte to gradually deteriorate, thereby reducing the electrochemical performance.
[0329] By comparing Example 1 with Examples 8-12, it can be seen that as the density (thickness) of the second coating layer gradually decreases, the cycle capacity retention rate and rate charge capacity retention rate of the battery basically show a trend of gradually increasing. This may be due to the gradual increase in the porosity of the composite electrode, which causes the wettability of the electrolyte to gradually improve, thereby improving the electrochemical performance.
[0330] It can be seen from Example 1 and Examples 13-14, and Comparative Example 2 and Example 15 that the porosity of the composite electrode is different when different pore-forming agents are used, and the cycle capacity retention rate and rate charging capacity retention rate of the battery with a large porosity are also slightly higher.
[0331] By comparing Example 1 with Examples 16-17, and by comparing Example 2 with Examples 18-20, it can be seen that within the range defined in the present application, as the content of the pore-forming agent increases, the porosity of the composite electrode gradually increases, and the cycle capacity retention rate and the rate charging capacity retention rate also gradually increase.
[0332] By comparing Example 1 and Example 21, it can be seen that, within the range defined in the present application, changing the type of ceramic has substantially no effect on the cycle capacity retention rate and the rate charge capacity retention rate.
[0333] By comparing Examples 1-3 and Comparative Examples 1-3, it can be seen that under the same active material, the present invention has a higher cycle capacity retention rate and rate charge capacity retention rate of the battery due to the presence of a pore former and a second material layer. This may be due to the gradual decrease in the porosity of the composite electrode, which causes the gradual deterioration of the wettability of the electrolyte and the subsequent decrease in electrochemical performance.
[0334] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0335] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0336] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A composite pole piece, characterized in that: include: current collector; A first material layer, the first material layer is disposed on at least a portion of the surface of the current collector, the first material layer comprises an active material and a pore former, the active material comprises a positive electrode active material or a negative electrode active material; The second material layer is arranged on at least part of the surface of the first material layer, and the second material layer includes ceramics; the interior and surface of the second material layer and the first material layer are both provided with a plurality of pores formed by thermal decomposition of at least part of the pore-forming agent.
2. The composite pole piece according to claim 1, characterized in that: The pore-forming agent includes at least one of ammonium carbonate, ammonium bicarbonate, azobisisobutyronitrile, and benzoyl peroxide; and / or, The particle size of the pore-forming agent ranges from 500 nm to 20 μm; and / or, The median particle size of the pore former is 1-5 μm; and / or, The mass content of the pore former in the first material layer is 0.1-3%.
3. The composite pole piece according to claim 1, characterized in that: The positive electrode active material includes at least one of lithium iron phosphate, ternary material, and lithium cobalt oxide; and / or, The negative electrode active material includes at least one of graphite, silicon-carbon composite material, silicon-oxygen compound and silicon; and / or, The ceramic includes at least one of alumina ceramic and boehmite; and / or, The particle size of the ceramic is in the range of 100 nm to 5 μm; and / or, The median particle size of the ceramic is 0.8-1.2 μm.
4. The composite pole piece according to claim 1, characterized in that: When the active material includes a positive electrode active material, the material of the first material layer includes the following components in mass percentage: 94-97% positive electrode active material, 0.5-2% first conductive agent, 1-3% first binder, 0.1-3% pore former; and / or, When the active material includes a negative electrode active material, the material of the first material layer includes the following components in mass percentage: 94-97% of the negative electrode active material, 0.5-2% of the second conductive agent, 0.7-2% of the thickener, 1-2% of the second binder, and 0.1-3% of the pore former; and / or, The second material layer includes ceramic and a third binder.
5. The composite pole piece according to claim 4, characterized in that: The first conductive agent includes at least one of conductive carbon black, Ketjen black, acetylene black and carbon nanotubes; and / or, The first binder includes at least one of polyvinylidene fluoride resin and polytetrafluoroethylene; and / or, The second conductive agent includes at least one of conductive carbon black, Ketjen black and acetylene black; and / or, The thickener comprises at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyvinyl alcohol and sodium polyacrylate; and / or, The second binder includes at least one of styrene-butadiene latex and polyacrylic acid; and / or, When the active material includes a positive electrode active material, the third binder includes at least one of an oil-based polyvinylidene fluoride resin, polyacrylic acid, and polymethyl methacrylate; and / or, When the active material includes a negative electrode active material, the third binder includes at least one of aqueous polyvinylidene fluoride resin, polyacrylic acid, and polymethyl methacrylate; and / or, The mass ratio of the ceramic to the binder is (5-9):(5-1).
6. The composite pole piece according to claim 1, characterized in that: When the active material includes a positive electrode active material, the composite electrode sheet is a positive electrode sheet, and the porosity of the composite electrode sheet is 30-40%; and / or, When the active material includes a negative electrode active material, the composite electrode sheet is a negative electrode sheet, and the porosity of the composite electrode sheet is 35-45%; and / or, The cohesive force of the composite pole piece is greater than 25 N / m and less than 50 N / m; and / or, The thickness of the remaining portion of the first material layer on the current collector is less than 5 μm after a peeling force test, and the peeling force is aN / m, 7<a<30; and / or, The surface density of the first material layer is 45-230 g / cm 2 and / or, The surface density of the second material layer is 5-20 g / m 2 and / or, The pore is a micro-nano pore channel, and the diameter of the pore is less than 1 μm; and / or, and / or, the temperature of the thermal decomposition is 100-120° C.; and / or, The current collector comprises one of copper foil, aluminum foil and carbon-coated aluminum foil; and / or, The thickness of the first material layer is 50-100 μm; and / or, The thickness of the second material layer is 5-20 μm; and / or, The mass ratio of the active material to the ceramic is (42.3-223.1):(2.5-18).
7. A method for preparing a composite pole piece according to any one of claims 1 to 6, characterized in that: include: Using a double-layer coating technology, the first slurry and the second slurry are simultaneously coated on the current collector to form a first coating layer and a second coating layer, respectively, to obtain a current collector containing a slurry layer; Drying and rolling the current collector containing the slurry layer to obtain the composite electrode sheet; The first slurry includes a material for the first material layer, and the second slurry includes a material for the second material layer.
8. The preparation method according to claim 7, characterized in that: The first slurry further includes a first solvent, and when the active material includes a positive electrode active material, the first solvent includes N-methylpyrrolidone (NMP), or, when the active material includes a negative electrode active material, the first solvent includes water; and / or, The second slurry further includes a second solvent, wherein the second solvent includes at least one of water and N-methylpyrrolidone (NMP); and / or, When the active material includes a positive electrode active material, the positive electrode active material is lithium iron phosphate, the solid content of the first slurry is 60-64%, and the viscosity of the first slurry is 7000-11000 MPa·s; or, the positive electrode active material is a ternary material, the solid content of the first slurry is 70-74%, and the viscosity of the first slurry is 6000-10000 MPa·s; or, the positive electrode active material is lithium cobalt oxide, the solid content of the first slurry is 76-80%, and the viscosity of the first slurry is 3000-7000 MPa·s; or, When the active material includes a negative electrode active material, the solid content of the first slurry is 52-56%, and the viscosity of the first slurry is 3000-7000 MPa·s; and / or, The solid content of the second slurry is 15-35%, and the viscosity of the second slurry is 3000-7000 MPa·s; and / or, The drying temperature is 100-120°C; and / or, The pore former is at least partially decomposed to generate gas during the baking process, so that a plurality of pores are formed inside and on the surface of the first coating layer and the second coating layer.
9. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The positive electrode sheet and / or the negative electrode sheet is a composite electrode sheet as described in any one of claims 1 to 6 or a composite electrode sheet prepared by the preparation method according to any one of claims 7 or 8.
10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Multilayer composite positive pole piece, method for preparing pole piece and lithium ion battery applying multilayer composite positive pole piece
CN104466188A
Negative pole piece as well as preparation method and application thereof
CN110993890A
Slurry, pole piece, battery cell, lithium ion battery and preparation method
CN116682973A
Electrode plate and secondary battery comprising same
CN116686153A
Negative electrode for lithium secondary battery, method for manufacturing negative electrode for lithium secondary battery, and lithium secondary battery comprising negative electrode
CN118511304A